Investigation of Wellbore Instability in Southern Rumaila Oil Field - Zaidan, Ali F.; Hadi, Farqad A.; Klempa, Martin (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study aims to address the issue by providing valuable insights into the factors contributing to the wellbore instability and proposing effective measures to mitigate the problem in the southern part of the Rumaila oil field. A comprehensive one-dimensional mechanical earth model (1D MEM) was developed by utilizing various logs data from 4 wells across the south part of this field, including gamma ray, bit size, caliper, bulk density, and sonic compression and shear logs. The model was validated with laboratory tests, including Brazilin and Triaxial tests, as well as repeated formation tests. To analyze the wellbore stability, three different failure criteria, namely Mohr-Coulomb, Mogi-Coulomb, and Modified lade, were employed. The results indicated that the Mogi-Coulomb criterion was the most accurate failure criterion in predicting rock failure. Wellbore instability problems had been observed across the shale sections throughout the Rumaila oil field, particularly through Tanuma, Khasib, top and bottom of Ahmadi, Nahr Umr, and Upper Shale members and Middle Shale members of Zubair formations. The 1D MEM results indicated that Shaly formations exhibited low stiffness rocks (low Young’s Modulus (YME)), low rock strength, and high Poisson’s ratio (PR), suggesting potential challenges related to wellbore instability in the Tanuma, top and bottom of Ahmadi, Nahr-Umr, and Zubair formations. A sensitivity analysis was performed to determine the safest mud weight and the optimum well trajectory for future drilling operations. According to the updated mud window of this field in 2023, the pressure in the Mishrif and Zubair formations was reinforced by injection wells, as it was noted that the pressure behavior shifted from depletion (2000 Psi). Based on the findings of this study, the good inclination of (0-25°) can be drilled with the mud weight of 1.24-1.26 sg, while the good inclination of (25-40°) can be drilled with the mud weight of 1.28-1.30 sg in all directions (i.e., all azimuths). The stress regime in most of the formations was found to be a strike-slip to a normal fault regime. The findings of this study can significantly benefit the oil industry and enhance overall productivity.